Coupling effect of fertigation and foliar application of micronutrients on growth, yield and quality of carnation (Dianthus caryophyllus) cv Bizet - DURGA, M LAKSHMI; JAWAHARLAL, M; KANNAN, M (The Indian Journal of Agricultural Sciences, 2016)
Investigation was undertaken to study the effect of fertigation and foliar application of micronutrients on growth, yield and flower quality of carnation (Dianthus caryophyllus L.) cv Bizet under naturally ventilated polyhouse at Nilgiris (Ooty) in Tamil Nadu during April 2012 to May 2013. The experiment consisted of nine micronutrient treatments and it was laid out in randomized block design with three replications. ZnSO4, FeSO4, CuSO4, Borax and chelated micronutrient EDTA mix (MN-EDTA) were given in different combinations through fertigation and/or foliar application. The effect of these micronutrients on vegetative growth, yield, quality was evaluated at critical crop growth stages. Results revealed that fertigation of 0.4% MN-EDTA+ foliar application of 0.2% MN-EDTA at fortnightly intervals, beginning from one month after planting up to harvesting stage significantly improved plant height (94.89 and 85.94 cm), number of leaves (184.62 and 215.98), number of laterals (6.8 and 9.4), earliness in flower bud appearance (94.75 and 80.20 days), stalk length (81.23 and 76.31 cm), yield (243.57 and 323.73 flowers/m2) and vaselife (16.20 and 16 days) during the two consecutive flushes, respectively.